Professor Molly Jahn on supporting people's food choices - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Although food security for all is a widely-held goal, it has not been achieved. Professor Jahn (University of Madison-Wisconsin, USA) on bringing US experiences and perspectives to the work of the commission, and bringing the commission's work to the farming community, policymakers and consumers in the U.S. Find out more at https://ccafs.cgiar.org/commission